The Contribution of Product Quality Perception in Predicting The Effectiveness of Digital Marketing Strategies: A Case Study on the Shopee Platform - Kusuma, Manggar Wulan; Wardhani, Shita Lusi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2025)
In the digital era, competition in the e-commerce industry is fiercer. Platforms like Shopee have become integral to consumers' lives in fulfilling their daily needs. To win the competition, Shopee sellers must develop innovative and effective marketing strategies. One of the most widely used strategies is a combination of event marketing, viral marketing, and affiliate marketing. Through a quantitative approach and SEM analysis, this study found that the three strategies had a significant positive influence on purchase intention. The unique finding is the central role of product quality perception as a mediator in this relationship, which highlights the importance of building a positive perception of product quality in supporting the success of marketing strategies in the digital age. By examining the influence of multi-channel marketing strategies and the mediating role of product quality perception, this study is expected to enrich our understanding of how consumers respond to various marketing stimuli on e- commerce platforms.